1997
DOI: 10.1182/blood.v89.11.3967
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Engraftment Without Significant Graft-Versus-Host Disease After Allogeneic Transplantation of CD34+ Selected Cells From Peripheral Blood

Abstract: We have prospectively evaluated the feasibility and results of the biotin-avidin immunoadsorption method (Ceprate SC system) for a phase I/II study of T-cell depletion of granulocyte colony-stimulating factor (G-CSF ) mobilized peripheral blood progenitor cells (PBPC) for allogeneic transplantation. Twenty consecutive patients, median age, 40 years (21 to 54) and diagnoses of chronic myeloid leukemia in chronic phase (n = 5), acute myeloblastic leukemia (n = 7), acute lymphoblastic leukemia (n = 2), chronic my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(38 citation statements)
references
References 22 publications
3
35
0
Order By: Relevance
“…Several series of CD34 þ selected PBPC have now been published (Link et al, 1996;Bensinger et al, 1996a;Urbano-Ispizua et al, 1997). Two studies (Link et al, 1996;Bensinger et al, 1996a) reported a high incidence of severe (grade II-IV) acute GVHD (60-80%) in patients receiving a CD3 þ cell dose of approximately 1 × 10 6 /kg when post-transplant cyclosporin alone was used for GVHD prophylaxis.…”
Section: Clinical Results Of Pbpc Transplantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several series of CD34 þ selected PBPC have now been published (Link et al, 1996;Bensinger et al, 1996a;Urbano-Ispizua et al, 1997). Two studies (Link et al, 1996;Bensinger et al, 1996a) reported a high incidence of severe (grade II-IV) acute GVHD (60-80%) in patients receiving a CD3 þ cell dose of approximately 1 × 10 6 /kg when post-transplant cyclosporin alone was used for GVHD prophylaxis.…”
Section: Clinical Results Of Pbpc Transplantsmentioning
confidence: 99%
“…Two studies (Link et al, 1996;Bensinger et al, 1996a) reported a high incidence of severe (grade II-IV) acute GVHD (60-80%) in patients receiving a CD3 þ cell dose of approximately 1 × 10 6 /kg when post-transplant cyclosporin alone was used for GVHD prophylaxis. Urbano-Ispizua et al (1997) recently updated the Spanish experience in 20 patients undergoing CD34 þ selected PBSC using CSA combined with prednisolone post-transplant. In this study they infused a median of 4·2 × 10 5 /kg CD3 þ cells and reported good engraftment with no cases of acute GVHD greater than grade I.…”
Section: Clinical Results Of Pbpc Transplantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts to enrich PBSCT by ex-vivo CD34 + cell selection (positive selection) have resulted in increased rates of GVHD, possibly by altering the cytokine expression patterns of transplanted cells or changing lymphocyte subsets delivered with the graft [25]. These efforts do not appear to alter engraftment kinetics significantly [25,26]. Negative selection (T cell depletion) clearly leads to lower rates of GVHD, at the expense of a slightly higher incidence of graft rejection.…”
Section: Engraftment and Kineticsmentioning
confidence: 99%
“…A potentially highly attractive and effective approach is the positive selection of CD34 + haematopoietic progenitor cells. The first phase II studies with CD34 + cell selected transplants using the Ceprate and Isolex devices were published in 1997 and showed encouraging results in terms of engraftment and GvHD incidence (Handgretinger et al , 1997; Urbano‐Ispizua et al , 1997). These devices are capable of reducing T cells by 3–5 logs and thus permit the use of haploidentical donors with a minimal incidence of GvHD (Reisner & Martelli, 2000; Martelli & Reisner, 2002).…”
mentioning
confidence: 99%